Problematika Penegakan Hukum Pidana Pemilu dalam Sistem Sentra Gakkumdu dan Rekonstruksinya Berbasis Pendekatan Restorative Justice - Cipto Hardoyo; Yasmirah Mandasari Saragih; Biner Sihotang (Pusat Riset dan Inovasi Nasional, 2026)
The enforcement of election criminal law plays a crucial role in safeguarding democratic integrity and upholding the principle of popular sovereignty. Law Number 7 of 2017 establishes the Integrated Law Enforcement Center (Sentra Gakkumdu) as a coordinated mechanism involving the Election Supervisory Body, the Police, and the Prosecution Service in addressing election crimes. However, in practice, the Gakkumdu system has not fully ensured a balanced realization of legal certainty, substantive justice, and legal utility. This study aims to analyze the problems of election criminal law enforcement within the Gakkumdu system, examine the relevance of the Restorative Justice approach in election law, and formulate a reconstruction of election criminal law enforcement based on this approach. This research employs normative legal research using statutory, conceptual, legal philosophy, and legal policy approaches. The findings indicate that the weaknesses in election criminal law enforcement arise from institutional fragmentation, normative ambiguity, and a legal culture dominated by legalistic and sectoral perspectives. The Restorative Justice approach is considered relevant as it prioritizes substantive justice and the restoration of democratic values. Therefore, reconstructing election criminal law enforcement based on Restorative Justice is essential to strengthening democratic legitimacy and public trust in elections in Indonesia.